Speaking the End Times: Early Modern Politics and Religion from Iberia to Central Asia - Green-Mercado, Mayte (Journal of the economic and social history of the Orient, 2018)
Abstract This introduction delineates the contours of early modern apocalyptic thought and practice among Christians, Muslims, and Jews by discussing specific themes explored in the five articles included in this special issue. It also situates the articles in the expansive scholarship on apocalypticism, highlighting the contribution of this collection of essays to the field. Paying close attention to and problematizing the importance of the terminology that expressed early modern notions of sacred history and political authority—in a context of intense inter-confessional contact and conflict—this introduction calls for a contextual examination of apocalyptic thought and practice.